From fronds to fish: the use of indicators for ecological monitoring in marine benthic ecosystems, with case studies from temperate Western Australia - Smale, D.; Langlois, T.; Kendrick, G.; Meeuwig, J.; Harvey, Euan (Springer, 2011)
Ecological indicators are used for monitoring in marine habitats the world over. With the advent of Ecosystem Based Fisheries Management (EBFM), the need for cost effective indicators of environmental impacts and ecosystem condition has intensified. Here, we review the development, utilisation and analysis of indicators for monitoring in marine benthic habitats, and outline important advances made in recent years. We use the unique, speciose benthic system of Western Australia (WA) as a detailed case study, as the development of indicators for EBFM in this region is presently ongoing, and major environmental drivers (e.g. climate change) and fishing practices are currently influencing WA marine systems. As such, the work is biased towards, but not restricted to, indicators that may be important tools for EBFM, such as biodiversity surrogates and indicators of fishing pressure. The review aimed to: (1) provide a concise, up-to-date account of the use of ecological indicators in marine systems; (2) discuss the current, and potential, applications of indicators for ecological monitoring in WA; and (3) highlight priority areas for research and pressing knowledge gaps. We examined indicators derived from benthic primary producers, benthic invertebrates and fish to achieve these goals.